2007
DOI: 10.1111/j.1572-0241.2007.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control Test Is a Simple Method to Diagnose Minimal Hepatic Encephalopathy and Predict Development of Overt Hepatic Encephalopathy

Abstract: ICT has good sensitivity/specificity for MHE diagnosis, is reliable and is equivalent to SPT for predicting OHE development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 21 publications
4
143
2
5
Order By: Relevance
“…In the healthy control group, a score of $14 ICT lures was seen in 31 of 95 (32.6%) subjects. Using the cut-off of >5 ICT lures proposed by Bajaj et al, 19,20 we observed that the number of healthy patients showing altered ICT increased to 81 of 95 (88.4%). Lure weighted by target accuracy or sum of PHES score and ICT lures did not further improve the diagnostic accuracy of PHES alone.…”
Section: Prevalence Of Minimal Hepatic Encephalopathymentioning
confidence: 89%
See 4 more Smart Citations
“…In the healthy control group, a score of $14 ICT lures was seen in 31 of 95 (32.6%) subjects. Using the cut-off of >5 ICT lures proposed by Bajaj et al, 19,20 we observed that the number of healthy patients showing altered ICT increased to 81 of 95 (88.4%). Lure weighted by target accuracy or sum of PHES score and ICT lures did not further improve the diagnostic accuracy of PHES alone.…”
Section: Prevalence Of Minimal Hepatic Encephalopathymentioning
confidence: 89%
“…19,20 Though ICT is easy to administer in an outpatient setting and showed good test-retest reliability, it did not have external validity for MHE because it did not predict either survival or number of the episodes of OHE on follow-up. Thus the ICT provided cognitive measures which were not up to the recommended diagnostic standards for cognitive investigation of MHE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations